Catch that crook! - Steele, Michael Anthony (New York : Scholastic, 2012)
A thief thinks he's found the perfect hiding spot after his latest heist: the LEGO City forest. But he wasn't counting on the Forest Police! It's a madcap chase of cops and robbers.
Accelerated Reader AR
Keywords: Police -- Juvenile fiction; LEGO toys -- Juvenile fiction; Beginning readers